China Road Safety Engagement Strategy : Interim Report - Bliss, Tony; Breen, Jeanne; Howard, Eric (World Bank, Washington, DC, 2013)
The World Bank's road safety partnership with the Government of China (GOC) is maturing at a time when a deeper awareness of the negative development impacts of road crashes in low and middle-income countries coincides with the shift in road safety management policies and practices in leading high-income countries which are becoming focused on the elimination of road deaths and serious injuries, rather than accepting them as human failure and the inevitable price of economic progress. This shift in results focus is also aligned with other sustainable development initiatives addressing environmental, energy and public health goals, which present significant opportunities to capture the co-benefits of harmonized initiatives. For these reasons the World Bank and GOC agreed to review the situation in China and prepare a new road safety engagement strategy. The proposed strategy aims to facilitate an accelerated transfer of road safety knowledge and scaling up of investment at national, provincial and city levels to rapidly improve China's road safety performance, with an emphasis on strengthening national lead agency functions and multisectoral coordination arrangements. It also aims to promote China's regional and global leadership role over the coming decade and draw upon the innovative services of international partners through the World Bank's global networks and road safety investment experience. The need for a designated agency to lead and coordinate the delivery of activities under the new engagement strategy was highlighted. Several candidate agencies were considered and in particular the State Administration for Work Safety (SAWS) was identified as being well placed and ready to take responsibility for this task.This report summarizes the review findings and presents them in an operational framework specified in the form of a project concept encompassing all activities proposed under the new engagement strategy. It then outlines the steps to be taken to finalize the project concept before detailed preparation for its implementation can commence.